Using lung evolution as a cipher for physiology - pathophysiology - Torday, John S. (Henry Stewart Talks, 2016)
Neutral Lipid Trafficking, Bronchopulmonary Dysplasia (BPD) as failed cell-cell interactions, PPARγ prevention of BPD, de Duve Hypothesis, Preventive Medicine, PTHrP, Glucocorticoid and βAdrenergic Receptor gene duplications, Oxygen effects on cell-cell interactions, Phylogeny of lung, kidney, heart, Skin-lung homology, Lung-kidney homology, Lung-brain homology, Predictive Model